2001
DOI: 10.1021/ie010383p
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Cell Adhesion to Bioreactive Surfaces in Shear:  The Effect of Cell Size

Abstract: Leukocyte adhesion under flow in the microvasculature is a multistep process in which rolling adhesion is followed by firm arrest. These interactions are mediated by binding between receptors on the leukocyte surface and complementary ligands on the surface of endothelial cells. Previous work using a computational method called "adhesive dynamics" showed that the general shape of a state diagram for cell adhesive behavior in flow could be predicted by the bond reaction rates and their dependence on force. Othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
(79 reference statements)
3
5
1
Order By: Relevance
“…It is seen that a larger diameter cell decreases the peeling time and increases the cell rolling velocity. This result is consistent with the simulation of Tees et al (2002) and experiments of Shinde Patil et al (2001). A larger cell causes a greater blockage of the vessel, which results in larger local hydrodynamic forces.…”
Section: Compound Drop Modelsupporting
confidence: 92%
“…It is seen that a larger diameter cell decreases the peeling time and increases the cell rolling velocity. This result is consistent with the simulation of Tees et al (2002) and experiments of Shinde Patil et al (2001). A larger cell causes a greater blockage of the vessel, which results in larger local hydrodynamic forces.…”
Section: Compound Drop Modelsupporting
confidence: 92%
“…For example, microbubbles designed to adhere to a post-capillary venule (lower shear rate) might be designed to be larger than those which would adhere to endothelial cells in the arterial circulation (higher shear rate) to prevent unwanted binding to these areas. This conclusion was previously suggested by Tees et al (Tees et al 2002), who examined the effects of microparticle size and applied shear rate on particle targeting to different targeting receptors(selectin-like, antibody-like, or streptavidin-like). Their results demonstrated that the types of adhesion that can be expected (rolling, transient, and firm) are a function of the type of targeting receptor (each of which has specific kinetic rate, bond compliance, and bond stiffness), particle radius, and shear rate.…”
Section: Discussionsupporting
confidence: 71%
“…We chose our design space to independently sample the kinetic rates based on the assumption that these types of molecules will likely have a narrow range of bond stiffness (σ) and compliance (γ). This assumption is not outside of convention as reported values for γ and σ have been within an order of magnitude independent of the bond type (Chang et al 2000b; Smith et al 1999; Tees et al 2002). To further validate this premise, we have performed a series of simulations where these parameters were varied independently of each other as well as the targeting receptor density on the surface of the microbubble (see Supplemental Data) and found that their effects are below the firm adhesion threshold for the receptor densities and ligand densities relevant to their clinical application.…”
Section: Discussionmentioning
confidence: 98%
“…Simulation of cell adhesion to bioactive surfaces has been reported (10). Leukocyte adhesion during flow in the microvasculature is known to be a multistep process.…”
Section: Discussionmentioning
confidence: 99%